REKOMENDASI PROMOSI JABATAN STRUKTURAL MENGGUNAKAN METODE FUZZY LOGIC PADA LPP RRI BUKITTINGGI - Yerix Ramadhani; Efitra Efitra; Darex Susanto (JSR : Jaringan Sistem Informasi Robotik, 2022)
Human resource management affects the development of an organization. Systematics in deciding the filling of structural positions and career paths of an employee can be carried out effectively and efficiently by implementing a decision support system. The application of the fuzzy logic method can provide an alternative for a Head of Station in determining employees, to fill a structural position. Decision support systems with fuzzy logic can be useful as a basis for consideration in decision making. So that the Station Head can make a decision to select appropriate employees to be promoted to structural positions in the positions of Head of Sub-Division of Administration, Head of Affairs, Head of Section and Head of Sub-Section at the LPP RRI Bukittinggi. The research was carried out by reviewing and evaluating the ongoing system so as to produce an assessment. The assessment has several attributes that are requirements for evaluation. These attributes are; managerial ability, competence and personality. The fuzzy logic method is considered very appropriate and has several advantages in supporting the decision on the feasibility level of an employee to be promoted.Keywords: Fuzzy Logic, Decision Support, Promotion, Staffing, Appraisal